Penerapan Metode Pembelajaran Fishbowl dalam Meningkatkan Keaktifan dan Hasil Belajar Siswa pada Mata Pelajaran Fiqih - Zuhrotul Mufidah; Nurul Azizah; Eko Saputra (IAIN Ponorogo, 2022)
This study aims to determine the application of the fishbowl method in increasing student activity and learning outcomes in fiqh subjects in class VIII A Pondok Pesantren Al-Madaniyah Jaro Kalimantan. The application of this method expecting to be a solution to overcome the problem of learning